PERFORMANCE AND NUTRIENTS UTILIZATION PARAMETERS OF BROILER CHICKENS ADMINISTERED VARIED DOSAGES OF Ocimum gratissimum LEAF EXTRACT - Ndubuisi-Ogbonna, Lois Chidinma; Ibeh, Ifeanyi Boniface; Adeboye, Mark Minecha; Adesada, Ayodeji Qudus; Olumide, Martha Dupe; Akintunde, Adeyinka Oye (FUDMA JOURNAL OF SCIENCES, 2025)
Ocimum gratissimum leaf extract has potential as a natural growth promoter due to its rich phytochemical composition. The study evaluated the performance of broiler chickens administered varied dosages of O. gratissimum leaf extract (OGLE). The study was conducted at Teaching and Research Farm, Babcock University, Ilishan-Remo, Ogun State, Nigeria. Four treatments with four replicates were designed with varying dosages of OGLE (0, 0.2, 0.4 and 0.6 Ml/ liter of water). A total of 160 Arbor Acre broiler chicks were randomly assigned in a completely randomized design. The study assessed growth and nutrient utilization parameters. The results showed that the administration of OGLE significantly affected (p
Keywords: Administration; Digestibility; Gut Morphology; Ocimum gratissimum Leaf Extract